Understanding human communication - Adler, Ronald B. (Ronald Brian) 1946-; Rodman, George R. 1948-; DuPré, Athena (Oxford University Press, 2014)
For over three decades, this has been the bestselling text for the Human Communication course. Understanding Human Communication is written with one goal in mind: to provide students with the insights and skills to succeed in our changing world. Fully updated and expanded to include more information on culture and communication, gender and communication, and the effects of technology and social media on communication, this twelfth edition also features two new types of boxes, "Understanding Diversity" and "@Work," as well as new annotated sample speeches.